2006
DOI: 10.1002/ijc.22066
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and integration sites of a murine C57BL/6 melanoma endogenous retrovirus involved in tumor progression in vivo

Abstract: Tumor development is a multistep process in which both genetic and epigenetic events cooperate for the emergence of a malignant clone with metastatic properties. The possibility that endogenous retroviruses promote the expansion of a neoplastic clone by subverting immunosurveillance has been proposed and recently demonstrated in the case of the B16 murine melanoma, which spontaneously express the melanoma-associated retrovirus (MelARV). Indeed, knocking down, by RNA interference, this endogenous retrovirus res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…RNAi suppresses melanoma cells in vitro and in vivo (Mangeney et al, 2005;Oricchio et al, 2007;Pothlichet et al, 2006;Serafino et al, 2009). There are several potential mechanisms to explain the role of HERV-Ks in melanomagenesis.…”
Section: Herv-k Expression Correlates With Mek and Cdk4 Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAi suppresses melanoma cells in vitro and in vivo (Mangeney et al, 2005;Oricchio et al, 2007;Pothlichet et al, 2006;Serafino et al, 2009). There are several potential mechanisms to explain the role of HERV-Ks in melanomagenesis.…”
Section: Herv-k Expression Correlates With Mek and Cdk4 Activationmentioning
confidence: 99%
“…There are several potential mechanisms to explain the role of HERV-Ks in melanomagenesis. First, HERV-K sequences may jump around by retro-transposition leading to mutagenesis and chromosomal abnormalities (Pothlichet et al, 2006;Tchenio & Heidmann, 1991) which may drive the evolution of aggressive clones. Second, HERV-K ENV, which is homologous to syncytin, may have fusogenic activity to mediate melanoma-melanoma and melanoma-target cell intercellular fusions and, therefore, can be the molecular link in the melanoma-normal cell fusion theory of metastasis (Carter, 2008;Pawelek & Chakraborty, 2008).…”
Section: Herv-k Expression Correlates With Mek and Cdk4 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] It has also been reported that, compared to healthy individuals, sera from patients with melanoma were much more likely to harbor HERV-K, ENV, and GAG antibodies. [49][50][51] The antibody concentration varied from 16%-22% depending on the study, but was negligible in healthy controls and correlated with worse prognosis.…”
mentioning
confidence: 99%
“…48 Another function of HERV-K in melanoma, proposed by Huang et al, 52 is the blockage of HERV-K by RNA interference and monoclonal antibodies in melanoma cells, resulting in a marked reduction in colonic growth of melanoma cells in vitro. 52 The down-regulation of the HERV-K reverse transcriptase by RNA interference or pharmacological inhibitors resulted in a lower mitotic rate and induced morphological differentiation, [52][53][54] and slowed down melanoma growth and formation of metastasis in vivo.…”
mentioning
confidence: 99%